Entrepreneurship Education and Family Support as Predictors of Entrepreneurial Intention: The Mediating Role of Entrepreneurial Experience among University Students - Patriandi Nuswantoro (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2025)
This study aims to analyze the influence of entrepreneurship education and family support on students’ entrepreneurial intention, with entrepreneurial experience as a mediating variable. A quantitative approach was employed using Path Analysis. Data were collected from 108 university students through an online questionnaire distributed via Google Forms, utilizing a Likert scale to measure four main variables: entrepreneurship education, family support, entrepreneurial experience, and entrepreneurial intention. Respondents were selected using a probability sampling technique. The results indicate that entrepreneurship education does not have a direct significant effect on entrepreneurial intention but has a positive influence on entrepreneurial experience. Family support shows a positive effect on both entrepreneurial experience and entrepreneurial intention. Furthermore, entrepreneurial experience positively affects entrepreneurial intention and serves as a mediator in the relationship between entrepreneurship education and family support on entrepreneurial intention. These findings highlight the crucial role of entrepreneurial experience as a bridge between entrepreneurial learning and family support in shaping students’ motivation to pursue entrepreneurship.